The Contribution of Betawi Ulama to Strengthening Islamic Education in Society - Nanda Khairiyah; Nahuda (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The development of Islam in Betawi from Jayakarta to Batavia and traces the pattern of Islamic diversity in Betawi. So it can be concluded that there is an intellectual relationship between the Nusantara clerics and the Makkah and Madinah clerics as well as the reform efforts carried out by the Betawi clerics. Islam and Betawi are inseparable. Even the term "Betawi" can only be used by native Jakarta residents who are Muslim. The contact of Islam with Betawi culture without causing conflict. This can happen because the Islam present in Betawi is more of the Shafi'i sect and understands the Sunnah Wal Jama'ah experts who tend to be more tolerant and inclusive and respect local culture and traditions. Thus, history also shows the peace, harmony, harmony that can be created over differences. Opinions may differ, but brotherhood must remain harmonious. This research uses qualitative research. The purpose of this study is to provide education to the Betawi people and as additional knowledge about the contribution and role of ulama in Betawi society